Dietary gluten alters the balance of pro‐inflammatory and anti‐inflammatory cytokines in T cells of BALB/c mice. Issue 1 (13th December 2012) - Antvorskov, Julie C.; Fundova, Petra; Buschard, Karsten; Funda, David P.
Summary Several studies have documented that dietary modifications influence the development of type 1 diabetes. However, little is known about the interplay of dietary components and the penetration of diabetes incidence. In this study we tested if wheat gluten is able to induce differences in the cytokine pattern of Foxp3+ regulatory T cells, as well as Foxp3− T cells, isolated from intestinal mucosal lymphoid tissue and non‐mucosal lymphoid compartments in BALB/c mice. The gluten‐containing standard diet markedly changed the cytokine expression within Foxp3− T cells, in all lymphoid organs tested, towards a higher expression of pro‐inflammatory interferon‐γ (IFN‐γ), interleukin‐17 (IL‐17) and IL‐2. In Foxp3+ regulatory T cells, gluten ingestion resulted in a mucosal increase in IL‐17 and IL‐2 and an overall increase in IFN‐γ and IL‐4. The gluten‐free diet induced an anti‐inflammatory cytokine profile with higher proportion of transforming growth factor‐β (TGF‐β)+ Foxp3− T cells in all tested lymphoid tissues and higher IL‐10 expression within non‐T cells in spleen, and a tendency towards a mucosal increase in TGF‐β+ Foxp3+ regulatory T cells. Our data shows that the gluten‐containing standard diet modifies the cytokine pattern of both Foxp3− T cells and Foxp3+ regulatory T cells towards a more inflammatory cytokine profile. This immune profile may contribute to the higher type 1 diabetes incidence associated with gluten intake.